Sizes Are Gendered: The Effect of Size Cues in Brand Names on Brand Stereotyping - Zhang, Kuangjie; Li, Shaobo (Kevin); Ng, Sharon (Journal of Consumer Research, 2022)
Abstract Size cues are increasingly common in brand names (e.g., Xiaomi and Mini Cooper), but scant research has investigated whether and how brand name size cues influence consumers’ perceptions. This research shows that a brand name size cue can evoke gender associations, which subsequently affect consumers’ perceived warmth and competence of the target brand. A series of seven studies provide converging evidence that brands with a size cue of smallness in the name are perceived to be warmer but less competent, while those with a size cue of bigness are perceived to be less warm but more competent. A combination of measurement-of-mediation and moderation-of-process approaches provide support for the role of gender associations underlying the effect of brand name size cues on consumers’ brand perceptions. This research also shows that brand name size cues can have diverging effects on the perceived warmth of the brand versus of the product. Finally, this research rules out alternative accounts based on perceived market power and firm size.